Comparison of the effectiveness of acceptance, commitment and mindfulness therapy on increasing psychological well-being and weight control in people with type 2 diabetes - Eisazadeh, Fatemeh; Saffarinia, Majid; Alipour, Ahmad; Aliakari Dehkordi, Mahnaz (International Journal of Applied Behavioral Sciences, 2022)
Background and Aim: Type 2 diabetes is a chronic and complex disease that requires constant medical and psychological care. Therefore, this study aimed to compare the effectiveness of acceptance, commitment and mindfulness therapy on increasing psychological well-being and weight control in people with type 2 diabetes. Materials and Methods: The research method was semi-experimental with pre-test-post-test design and two-month follow-up with the control group. The statistical population of this study included men with type 2 diabetes and overweight in Tehran in 2021. 60 patients were selected by purposive sampling method and randomly divided into three equal groups, including experimental group A (under acceptance and commitment therapy), experimental group B (under mindfulness therapy), and control group (without intervention). Data collection tools in this study were Reef Psychological Well-Being Questionnaire (1989), and calculation of BMI for weight control. Data were analyzed using repeated measures analysis of variance. Results: The results showed that there was a significant difference between the mean scores of psychological well-being and weight control of the acceptance and commitment therapy group and the control group (p <0.001). Also, there was a significant difference between the scores of psychological well-being and weight control of the mindfulness therapy group and the control group (p <0.05). Conclusion: It can be concluded that both therapies, especially the therapy based on acceptance and commitment, are effective methods in reducing the psychological and physical problems of patients with type 2 diabetes.